Pollen Analysis Revealing the Paleoenvironment of a 3520 years B.P. old Sediment in the Guanabara Bay, Rio de Janeiro, Brazil - Barth, Ortrud Monika; Barreto, Cintia Ferreira; Vilela, Claudia Gutterres; Baptista-Neto, José Antônio (Anuário do Instituto de Geociências, 2011)
The intention of the present investigation was to understand the dynamic of different types of vegetation that occurred in the Guanabara Bay region, Rio de Janeiro, during the recent Holocene, analyzing a sediment level of conventional 3520 À 50 years B.P. old, obtained in the Jurujuba sound. Palynological analysis of the sediment showed dominance of the Ombrophilous Forest, and plant taxa of the field vegetation were not frequent. Environment conditions were favorable to hygrophyte plant development. Similar dynamic of this transgressive sea level event was detected also in other coastal areas of the state of Rio de Janeiro, far from the Guanabara Bay.